Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.

Simplify.
Please give an explanation or step-by-step answer.


SimplifyPlease Give An Explanation Or Stepbystep Answer class=

Sagot :

[tex]\dfrac{2y}{y^2-9y+18}-\dfrac{1}{y-6}=\\ \dfrac{2y}{y^2-3y-6y+18}-\dfrac{1}{y-6}=\\ \dfrac{2y}{y(y-3)-6(y-3)}-\dfrac{1}{y-6}=\\ \dfrac{2y}{(y-6)(y-3)}-\dfrac{1}{y-6}=\\ \dfrac{2y}{(y-6)(y-3)}-\dfrac{y-3}{(y-6)(y-3)}=\\ \dfrac{2y-y+3}{(y-6)(y-3)}=\\ \dfrac{y+3}{(y-6)(y-3)}[/tex]